KNOWLEDGE, ATTITUDE AND PRACTICE SURVEY REGARDING CLASS II COMPOSITE RESTORATION AMONG DENTAL STUDENTS - naram, Abhishek; S, Deepak (International Journal of Psychosocial Rehabilitation, 2019)
Composite resins are currently the most popular of all tooth coloured restorative materials, which completely replaced silicate cement and acrylic resin as esthetic restorative material. The aim of this KAP survey was to assess the level of awareness and clinical practice among the undergraduate students regarding class II composite restoration. An online survey was done with the structured questionnaire based on knowledge, attitude, practice among the dental students and it was distributed among 100 undergraduate students via electronic media. Data entry was done in the Excel sheet and SPSS software was used to analyze the data. The majority of the participants were interns (45%), Statistical analysis, Chi square test was used to assess the association between the year of study and the responses. And the results are depicted in the form of a bar chart. The results showed that dental students have fair knowledge on restoration of class II composite. There is a need for awareness on recent material characteristics and restoration techniques for undergraduate dental students on class II composite restorations in order to achieve desired results and esthetics within a stipulated time.